Institute of Metals Division - Discussion: Factors Affecting the Strength of Iron Rich Iron- Molybdenum-Boron Alloys - H. J. Beattie (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
R. L. Stegman and M. R. Achter (U.S. Naval Research Laboratory)—In a study of the surface structures developed in the fatigue of nickel at low strains as a function of temperature, we have obtained similar results.3 As our apparatus permits fatigue tests to be conducted in vacuo, there was no masking of the surface at high temperatures by oxidation so that the structures there could be observed directly. The relatively few broad slip bands observed at room temperature gave way at 300°C to a large number of uniformly distributed and narrower slip bands. At 550°C deformation began to concentrate around the grain boundaries and progressively increased up to 800°C. In addition fatigue strength was observed initially to increase with increasing temperature up to about 600°C due to the effectively increased ductility caused by the dispersal of fatigue damage. The fatigue strength then decreased at higher temperatures as grain boundary cracking dominates. Maria Ronay, W. H. Reimann, and W. A. Wood (authors' reply)— The authors are pleased to note that R. L. Stegman and M. R. Achter reach similar conclusions from their study of surface slip on nickel. However, they would emphasize that their own conclusions are based on what is shown by study of specimens that have been sectioned and that this study also shows that surface slip is not necessarily representative of what happens below the surface.